Design of a Web-Based SimAgri Plantation Management Information System at SMKS Bakti Agro Mandiri - Alfauzan Hakiki; Usman Usman (Jurnal Armada Informatika, 2026)
This study aims to address management obstacles in the Plantation Crops Agribusiness (ATP) major at SMKS Bakti Agro Mandiri, where practices are currently conducted conventionally using physical logbooks. The primary issues identified include slow harvest data recapitulation, risks of inventory data loss, and suboptimal utilization of student gadgets for productive field activities. The system was developed using the Agile Software Development Life Cycle (SDLC) method, selected for its flexibility in accommodating iterative user requirement changes, with a relational database designed in MySQL via phpMyAdmin. The results demonstrate the creation of a mobile-friendly, web-based Garden Management Information System (Simagri). This system effectively integrates planning, inventory, and real-time harvest reporting functions. The study concludes that the implementation of Simagri significantly improves garden operational efficiency, minimizes the risk of losing planting history, and optimizes student smartphone usage as a transparent productivity instrument.